دور المشاريع الصغيرة والمتوسّطة في علاج مشكلة البطالة - إدريس، هنادي محمد; العكام، محمد خير (جامعة البعث, 2016)
Due to the problem of unemployment of adverse effects at all levels of social, economic and political in could threaten the stability of societies, so it was necessary to work to find solutions to this serious problem, small and medium enterprises was one of these solutions to meet them, and the importance of this matter dealt with the pages of this paper the concept of unemployment defined as the types and causes of it in the first section, the concept of small and medium enterprises in terms of the various definitions, characteristics and their importance and their role in reducing the worsening problem of unemployment, in the second topic of it.
نظرا لما لمشكلة البطالة من آثار سلبية على كافة الصعد الاجتماعية والاقتصادية والسياسية بشكل يمكن أن يهدد استقرار المجتمعات، لذلك كان من الضروري العمل على إيجاد الحلول لهذه المشكلة الخطيرة، فكانت المشروعات الصغيرة والمتوسطة إحدى هذه الحلول لمواجهتها، ولأهمية هذا الأمر تناولت صفحات هذا البحث مفهوم البطالة من حيث تعريفها وأنواعها وأسبابها في المبحث الأول منه، ومفهوم المشروعات الصغيرة والمتوسطة من حيث تعاريفها المختلفة وخصائصها وأهميتها ودورها في الحد من تفاقم مشكلة البطالة، وذلك في المبحث الثاني منه.
Keywords: البطالة -- المشاريع الصغيرة والمتوسّطة -- التنمية الاقتصادية